CMLS STRATEGIC PARTNERSHIP WITH IDP EDUCATION LIMITED FOR IELTS EXCELLENCE - Umi Kalsom, Masrom; Fatimah, Ali (Pusat Bahasa Moden (PBM), 2024)
24 January 2024 - It was with great pleasure that Centre for Modern Languages (CML) received a visit from Mr. Thinesh Amaresin and Mr. Ravi R Krishnan of IDP Education Limited. Playing a crucial role in streamlining the International English Language Testing System (IELTS) exam process in Malaysia, IDP Edu. Ltd. contributes to educational progress and the global mobility of students.